Hidden Sacrifices: Narratives of Select Filipina Overseas Workers in Southeast Asia - Tugano, Axle Christien (Social Sciences and Development Review, 2022)
In my essay “Chasing Waves: Reflection on Southeast Asian Fisherfolk (2021a),” I already featured the less documented experience of the socially marginalized. My essay focused on the personal narratives of Bruneian fishermen of Kampor Ayer, Brunei Darussalam (2016); the fishermen of Mui Ne, Vietnam (2017); and the Intha of Myanmar (2018), with whom I had the fortunate chance to converse with. However, my personal travel experience in the three countries only gave voice to “non-Filipino workers.” That is why in this current essay, I will highlight the unique experience of the Filipinos themselves – in the form of migrant workers in Southeast Asia. I have interacted with and interviewed many Overseas Filipino Workers (OFWs) in Europe, Asia, Australia, and the Pacific; even in other countries where Filipino tourists were unfamiliar or visited, surprisingly happen to have OFWs. With that, it is unsurprising why Filipinos are articulated as globe-trotting people (Perdon 2014) and quasi-wandering people (San Juan 2009) because of their prevalence in the discourse of the global diaspora. In this essay, I will feature the stories of personal experiences of select Filipina workers in Southeast Asia, specifically in Malaysia (2014), Singapore (2014), and Cambodia (2017), extracted from my travel narratives from 2014-2018.